MAKING SENSE OF GRAMMAR IN ENGLISH THROUGH PRACTICING THE DIALOGUES - Jannah, Nor (LET: Linguistics, Literature and English Teaching Journal, 2012)
The purpose of this paper is to reveal the way of the English Department students at the University of Lambung Mangkurat  in making sense of grammar in English that they have learnt for about six years or more.  It is a matter of fact that those students have learnt English grammar mostly for more than five years. However they still cannot feel the sense of grammar while using it.  Therefore, they often seem confused which part of grammar to be used between one occasion to another.  By practicing the dialogues, those students can sharpen their senses of grammar of English.